2011
DOI: 10.1002/ibd.21431
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical characteristics in hispanic and non-hispanic whites with ileal pouch–anal anastomosis: A case–control study

Abstract: There appeared to be some difference in the preoperative characteristics of patients who underwent colectomy for UC between Hispanics and non-Hispanic whites, but outcomes after the restorative proctocolectomy with IPAA were comparable. Further studies are needed to characterize the natural history of UC and IPAA in the Hispanic population and the associated biosocioeconomic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
3
1
1
Order By: Relevance
“…This is reassuring and in agreement with other studies that showed no difference in complication rates and outcomes after IPAA between Blacks, Hispanics, and Whites. 29 , 30 However, our data contrast with other studies that showed that composite postoperative morbidity after elective surgeries for IBD was highest for Black patients 31 and that non-White patients had increased odds of individual complications after surgery for IBD. 32 It is important to point out that those studies did not specifically evaluate IPAA surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…This is reassuring and in agreement with other studies that showed no difference in complication rates and outcomes after IPAA between Blacks, Hispanics, and Whites. 29 , 30 However, our data contrast with other studies that showed that composite postoperative morbidity after elective surgeries for IBD was highest for Black patients 31 and that non-White patients had increased odds of individual complications after surgery for IBD. 32 It is important to point out that those studies did not specifically evaluate IPAA surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…24 Currently, the proctocolectomy rate has decreased from 10.2 % to 5.1 %, and this may be related to an earlier and more efficient control of the disease; the comparison in other studies between Hispanic and non-Hispanic patients shows a high rate of ileal pouch failure in the former group, while a higher rate of surgical procedures was documented in the latter group. 25 In conclusion, CIUC in Latin America has a different phenotype in comparison with other areas of the world and has shown behavioral changes over time that should be addressed from a diagnostic and therapeutic perspective. In the present work, we identified an increase in the frequency of pancolitis, presence of EIM and anti-TNF therapy prescription; in addition, the rate of proctocolectomy has decreased in recent years.…”
Section: Discussionmentioning
confidence: 96%
“…24 En la actualidad, la tasa de proctocolectomía disminuyó del 10.2 al 5.1 % y esto puede relacionarse con un control de la enfermedad más temprano y eficiente; la comparación en otros estudios entre pacientes hispanos y no hispanos demuestra una tasa elevada de falla en el reservorio ileal en el primer grupo, mientras que se documentó una mayor tasa procedimientos quirúrgicos en el último grupo. 25 En conclusión, en América Latina la CUCI tiene un fenotipo diferente en comparación con otras áreas del mundo y ha presentado cambios en su comportamiento a lo largo del tiempo que deben ser atendidos desde una perspectiva diagnóstica y terapéutica. En el presente trabajo identificamos un aumento en la frecuencia de pancolitis, presencia de MEI y prescripción de terapia anti-TNF; además, en los últimos años ha disminuido la tasa de proctocolectomía.…”
Section: Discussionunclassified